2021
DOI: 10.1002/2211-5463.13351
|View full text |Cite
|
Sign up to set email alerts
|

The HIF‐1α pathway plays a critical role in salivary gland development in ex vivo organ cultures

Abstract: The transcription factor, hypoxia‐inducible factor‐1α (HIF‐1α), has previously been shown to upregulate the expression of hypoxia‐related genes, including erythropoietin (EPO). However, the role of hypoxia‐inducible factor‐1α in morphogenesis during salivary gland development is unclear. We investigated the function of HIF‐1α in submandibular gland (SMG) organ cultures obtained from embryonic day 13.5 embryos from ICR female mice. Expression of HIF‐1α, glucose transporter 1, and vascular endothelial growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Many signaling pathways are involved in salivary gland development, and challenges with environmental changes (hypoxic stimulation) or pharmacological inhibitors enables study of these pathways. Hypoxic stimulation is involved in the development of various organs (Dunwoodie, 2009), and recent studies have revealed a key role for HIF in salivary gland development (Dunwoodie, 2009;Kimura et al, 2022). Signal inhibitors U0126, which inhibits PI3K; LY294002, which inhibits AKT; and rapamycin, which inhibits mTOR, have been used in development studies that have also suggested a role for these pathways in salivary gland development (Larsen et al, 2003;M.…”
Section: Analysis Of Salivary Gland Development Under Hypoxic Stimula...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many signaling pathways are involved in salivary gland development, and challenges with environmental changes (hypoxic stimulation) or pharmacological inhibitors enables study of these pathways. Hypoxic stimulation is involved in the development of various organs (Dunwoodie, 2009), and recent studies have revealed a key role for HIF in salivary gland development (Dunwoodie, 2009;Kimura et al, 2022). Signal inhibitors U0126, which inhibits PI3K; LY294002, which inhibits AKT; and rapamycin, which inhibits mTOR, have been used in development studies that have also suggested a role for these pathways in salivary gland development (Larsen et al, 2003;M.…”
Section: Analysis Of Salivary Gland Development Under Hypoxic Stimula...mentioning
confidence: 99%
“…Many signaling pathways are involved in salivary gland development, and changing the environment (hypoxic stimulation) or subjecting the culture to signaling pathway inhibitors enables exploration of the signaling pathways involved in development. Hypoxic stimulation is involved in the development of various organs and has been used to examine the function of hypoxia‐inducible factor (HIF) (Dunwoodie, 2009; Kimura et al., 2022). Signaling inhibitors used in developmental studies include the small molecule U0126, which inhibits PI3K signaling; LY294002, which inhibits AKT signaling; and rapamycin, which inhibits mTOR signaling (Larsen et al., 2003; M. Sakai et al., 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%